2019
DOI: 10.18332/tpc/113105
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of family counselling on reducing exposure to secondhand smoke at home among pregnant women in Iran

Abstract: INTRODUCTION Pregnant women are often exposed to secondhand smoke that affects them and their child. Our aim was to determine the effectiveness of family counselling using the BASNEF model on reducing exposure to secondhand smoke at home among pregnant women. METHODS A quasi-experimental study was conducted on 103 pregnant women exposed to secondhand smoke. They were selected using a multistage cluster sampling method and allocated into intervention (50 people) and control (53 people) groups. Four family couns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Meanwhile, the other three studies applied the clinical intervention where trained healthcare providers are given the responsibility to implement the intervention in a clinic or hospital-based setting. 15,17,18 The works of literature show that the involvement of healthcare providers in giving at least minimal advice on SHS exposure in pregnancy during antenatal visits further supports the idea that combining theory-driven intervention with clinical intervention maximizes the effect of preventive intervention. Hence, additional studies are required to determine the efficacy of the combination of theories and clinical intervention.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Meanwhile, the other three studies applied the clinical intervention where trained healthcare providers are given the responsibility to implement the intervention in a clinic or hospital-based setting. 15,17,18 The works of literature show that the involvement of healthcare providers in giving at least minimal advice on SHS exposure in pregnancy during antenatal visits further supports the idea that combining theory-driven intervention with clinical intervention maximizes the effect of preventive intervention. Hence, additional studies are required to determine the efficacy of the combination of theories and clinical intervention.…”
Section: Discussionmentioning
confidence: 88%
“…14 Only one study included both pregnant women and their smoking spouses in preventative intervention to improve the effectiveness of the intervention. 18 Even so, the works of literature showed that participation of both pregnant women and their smoking spouses is an important strategy to help pregnant women protect themselves from SHS exposure and simultaneously encourage their smoking spouses to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study confirmed that motivational interviews could significantly reduce the exposure to secondhand smoke in the pregnant women in the intervention group compared to the control group. Similarly, Soltani et al showed that family counseling had a positive effect on decreasing the exposure to secondhand smoke at home among a sample of pregnant women ( 25 ).…”
Section: Discussionmentioning
confidence: 97%
“…These highlights the necessity of SHS prevention intervention to educate the public on the harmful effects of SHS exposure toward pregnant women and their unborn babies, particularly to smoking spouses as the main source of SHS exposure at home 10,[13][14] The content of the intervention should emphasize both pregnant women and their smoking spouse since most of the interventions do not directly target that husband who smokes but provide the intervention to non-smoking pregnant women on ways to help their smoking husband to quit thus the real outcome of the intervention are inconclusive 15 . In addition, the involvement of smoking spouses in ensuring the health of their pregnant wives is important to increase awareness of the dangers of smoking and increase sensitivity to the need to prevent SHS exposure at home 16 . Pregnancy can be a motivating factor for changing the behavior of a smoking spouse 14 .…”
Section: Introductionmentioning
confidence: 99%